К вопросу о презентации гендерной идентичности поколения «Y» (на примере российской культуры) - Zubareva S. S. (Новое слово в науке: перспективы развития, 2016)
The article analyzes the presentation of gender identity in the Russian media space, have an impact on the mental aspects of the consciousness of the Russian youth. QMS analyzes and media content are popular among the generation of «Y». For example, Russian information products the author examines the formation of images of both sexes.
Keywords: социальное поведение; ментальность; гендерная идентичность; репрезентация; representation; gender identity; generation of «Y»; social behavior; mentality; поколение «Y»; полоролевая дифференциация